Seasonal monitoring of dissolved and particulate algal biotoxins in the northern Salish Sea using high performance liquid chromatography and tandem mass spectrometry - Andrew R.S. Ross; Béatrice Ip; Mackenzie Mueller; Blair Surridge; Harry Hartmann; Navinder Hundal; Nathan Matthews; Hayleigh Shannon; Melissa Hennekes; Akash Sastri; R. Ian Perry (Harmful Algae, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Corrigendum to ‘The effect of ambient temperatures on hospital admissions for kidney diseases in Central Australia’ [Environ. Res. 259 (2024) 119502] - Mohammad Radwanur Talukder; Md Tauhidul Islam; Supriya Mathew; Chris Perry; Dung Phung; Shannon Rutherford; Alan Cass (Environmental Research, 2024)

The effect of ambient temperatures on hospital admissions for kidney diseases in Central Australia - Mohammad Radwanur Talukder; Md Tauhidul Islam; Supriya Mathew; Chris Perry; Dung Phung; Shannon Rutherford; Alan Cass (Environmental Research, 2024)

Domoic acid in Canadian Pacific waters, from 2016 to 2021, and relationships with physical and chemical conditions - R. Ian Perry; Nina Nemcek; Melissa Hennekes; Akash Sastri; Andrew R.S. Ross; Hayleigh Shannon; Ryan B. Shartau (Harmful Algae, 2023)

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

The Ocean as a Classroom: Considering the Roles of Equity, Diversity, and Justice in Oceanographic Knowledge Production to Promote Accessibility for Future Generations - Natalia Erazo; Tricia Light; Dante Capone; Anna Effinger; Pierina Erazo; Linqing Huang; Ankitha Kannad; Kaycie Lanpher; Emmet Norris; Shannon Perry; Emilio Romero; Tamara Russell; et al. (Oceanography, 2023)
Understanding the history of how we studied our ocean in the past and how we study it now will help us develop approaches to make future oceanographic knowledge production more diverse, accessible, and inclusive. The motto of the UN Decade of Ocean Science for Sustainable Development (2021–2030) is, “The ocean we need for the future we want” (Singh et al., 2021). The Ocean Decade gives the ocean sciences community an opportunity to change the way it conducts research, to use ocean science to support sustainable development, and to energize the ocean sciences for future generations. With these goals in mind, we developed an introductory level, student-led graduate seminar that builds on the Ocean Decade framework. A research cruise involving seminar participants followed the seminar sessions. Here, we discuss how we conducted the seminar and highlight directions that are needed to energize future generations of ocean leaders and make ocean science more equitable, inclusive, and accessible.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

Identification and evaluation of quantitative trait loci underlying resistance to multiple HG types of soybean cyst nematode in soybean PI 437655 - Yongqing Jiao; Tri D. Vuong; Yan Liu; Clinton Meinhardt; Yang Liu; Trupti Joshi; Perry B. Cregan; Dong Xu; J. Grover Shannon; Henry T. Nguyen (Theoretical and Applied Genetics, 2015)

QTL, additive and epistatic effects for SCN resistance in PI 437654 - Xiaolei Wu; Sean Blake; David A. Sleper; J. Grover Shannon; Perry Cregan; Henry T. Nguyen (Theoretical and Applied Genetics, 2009)

Fishing for Answers with Transposons - Shannon A. Wadman; Karl J. Clark; Perry B. Hackett (Marine Biotechnology, 2005)